Reference Ranges for Vermis Biometry on Prenatal Ultrasound: Systematic Review and Meta-Analysis - Rosenbloom, Joshua I; Yaeger, Lauren H.; Porat, Shay (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Purpose To conduct a systematic review and meta-analysis of published nomograms for fetal vermis biometry.Materials and Methods A structured literature search was conducted to identify studies that reported normal measurements of the fetal vermis. A customized quality assessment tool was used to review the selected articles. Random effects meta-analysis was used to calculate normal ranges for vermian craniocaudal diameter, anteroposterior diameter, and surface area.Results A total of 21 studies were included for qualitative review and 3 studies were included for quantitative synthesis. The 3 included articles comprised a total of 10 910 measurements from gestational ages 17–35 weeks. The quality assessment demonstrated that there was generally poor reporting regarding maternal characteristics and neonatal outcomes. Except for one article with a large sample size, the mean number of fetuses per week of gestational age was 15.9, with the lowest number being 5. There was significant statistical heterogeneity. Non-visualization rates ranged from 0–35.4 %. The craniocaudal diameter (reported in 3 articles) increased from a mean of 7.90 mm (95 % confidence interval [CI] 7.42, 8.38) at 17 weeks to 21.90 mm (95 % CI 20.63, 23.16) at 35 weeks gestation. The anteroposterior diameter (reported in 2 articles) increased from 6.30 mm (95 % CI 5.42, 7.18) at 17 weeks to 15.85 (95 %CI 15.49, 16.21) at 32 weeks.Conclusion Reference ranges for vermis biometry across gestation based on meta-analysis of existing references are provided. However, because many of the underlying studies suffered from significant methodological issues, the ranges should be used with caution.
Keywords: obstetrics; neurology; vermis